The Comparison of Microleakage between Bioactive Composite Resin and Compomer - Fani Pangabdian; Yongki Hadinata Wijaya; Dwi Acti Widyanita (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: The ideal restoration material should have endurance, compatible with tooth structure and visible surrounding tissues and must be able to restore the lost tissue. There are various restoration materials such as Compomer and Bioactive Composite Resin. Microleakage is one of the failure in surface sealent, and this may increase the risk of secondary caries. Purpose: The aim of this study was to prove and compare the differences of microleakage between Compomer and Bioactive Composite Resin in class I restoration. Material and Method: Maxilla’s first premolar teeth with class I cavities (diameter: 3mm, depth: 3mm) divided into two groups with 10 samples each group. Group I: Compomer (Dentsply), Group II: Bioactive Composite Resin (Activa Pulpdent USA). All group were immersed in 1% methylene blue solution for 24 hours, rinsed in running water, and section mesial-distal using carborundum disc. Afterward, section were assessed for dye penetration that represent the mickroleakage using scoring method under digital microscope. Finally data were collected and statistically analyzed. Result: There were significant differences between each group (p<0.05). Microleakage in restoration with Bioactive Composite Resin (1.7) shows smaller values than Compomer restoration (4.4). Conclusion: This research show that there is differentiation of microleakage between Compomer and Bioactive Composite Resin. In Bioactive Composite Resin found the smallest microleakage.